2019
DOI: 10.1029/2018gb005985
|View full text |Cite
|
Sign up to set email alerts
|

Insights From the238U‐234Th Method Into the Coupling of Biological Export and the Cycling of Cadmium, Cobalt, and Manganese in the Southeast Pacific Ocean

Abstract: Better constraints on the magnitude of particulate export and the residence times of trace elements are required to understand marine food web dynamics, track the transport of anthropogenic trace metals in the ocean, and improve global climate models. While prior studies have been successful in constructing basin‐scale budgets of elements like carbon in the upper ocean, the cycling of particulate trace metals is poorly understood. The 238U‐234Th method is used here with data from the GP‐16 GEOTRACES transect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 110 publications
(211 reference statements)
4
26
0
Order By: Relevance
“…Total 238 U was derived from salinity (Owens et al, 2011). Steady‐state assumptions were made, and lateral advection of 234 Th was determined to be negligible when these calculations were possible (e.g., along transects where a 234 Th gradient and current speeds could be determined) or where prior studies had already indicated that these assumptions were valid (Black et al, 2019; Lemaitre et al, 2018; Owens et al, 2015). For the new locations in this study, upwelling was a significant factor for the coastal region of the Pacific campaign only, and the appropriate adjustments were made (Black et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Total 238 U was derived from salinity (Owens et al, 2011). Steady‐state assumptions were made, and lateral advection of 234 Th was determined to be negligible when these calculations were possible (e.g., along transects where a 234 Th gradient and current speeds could be determined) or where prior studies had already indicated that these assumptions were valid (Black et al, 2019; Lemaitre et al, 2018; Owens et al, 2015). For the new locations in this study, upwelling was a significant factor for the coastal region of the Pacific campaign only, and the appropriate adjustments were made (Black et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…2) are similar to those seen in the open ocean (see compilations in Owens et al, 2011, andVan Der Loeff et al, 2006, andreferences therein). It thus appears that water column suboxic/anoxic conditions alone are not sufficient to remove U, in contrast to sedimentary U studies underlying lowoxygen waters where soluble U(VI) diffuses downward into subsurface sediments and is reduced to insoluble U(IV) (Anderson et al, 1989;Böning et al, 2004;Scholz et al, 2011). Our inference is in accord with water column 238 U studies in intense OMZs in the eastern tropical North Pacific (Nameroff et al, 2002) and the Arabian Sea (Rengarajan et al, 2003), where 238 U concentrations remain constant over the entire upper water column studied.…”
Section: Lack Of Linear 238 U-salinity Correlation In the Peruvian Omzmentioning
confidence: 75%
“…Black et al (2019) reported no significant differences in SSF and LSF pP: 234 Th, pCo: 234 Th and pCd: 234 Th ratios contrasting with the higher pMn: 234 Th ratios in the LSF compared to the SSF, leading to a greater contribution of the LSF to the total pMn flux 36 .…”
Section: Component: 234 Th Ratios and Export Fluxesmentioning
confidence: 99%
“…Large particles (>53µm) are generally assumed to represent the sinking particulate matter and are thus responsible for the particulate export flux [77][78][79] . Using the component: 234 Th ratios from the LSF to calculate export fluxes is the most common approach 36,[80][81][82][83] . However, recent studies have shown that the SSF could also contribute to the export flux of particulate carbon or nitrogen in oligotrophic regions 20,21,84 .…”
Section: Component: 234 Th Ratios and Export Fluxesmentioning
confidence: 99%
See 1 more Smart Citation